Sounding Like an Angel, Attacking Like a Viper: Victimhood Construction in Scam Emails - Ajayi, Temitope Michael; Oyetoro, Obadiah Blessing; Ogundare, Olamide Comfort (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2024)
Given the security and economic risk it poses to the global space, the phenomenon of cybercrime has enjoyed scholarly attention from different disciplines. However, no serious attention has been paid to victimhood construction in scam emails, particularly how scammers deploy linguistic/discursive resources to portray themselves as victims of ‘false’ circumstances to get the better part of their targets. Thus, this study, resting on van Dijk’s Critical Discourse Analysis and a fusion of insights from four socio-cognitive approaches to theories of persuasion, investigates the discursive strategies for achieving victimhood construction in scam emails. Data comprised excerpts from 20 purposively sampled emails retrieved from the researchers’ spam folders. To appeal to emotional sentiments, scammers often project themselves as victims of terminal diseases, orphanhood, corrupt political space or widowhood. Findings revealed actor description, number game, evidentiality, situation description, self-denigration, and power strategies, are prominent discursive elements deployed in creating victimhood in scam emails.